2021
DOI: 10.1016/j.jmig.2021.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Technicity in Canada: A Nationwide Whole-Population Analysis of Temporal Trends and Variation in Minimally Invasive Hysterectomies

Abstract: Measurements and Main Results: A total of 369 520 hysterectomies were performed in Canada during the 10-year period, during which the hysterectomy rate decreased from 313 to 243 per 100 000 women. The proportion of abdominal hysterectomies decreased (59.5% to 36.9%), laparoscopic hysterectomies increased (10.8% to 38.6%), and vaginal hysterectomies decreased (29.7% to 24.5%), whereas the national technicity index increased from 40.5% to 63.1% (p <.001, all trends). The median length of stay decreased from 3 (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…[22][23][24] With advances in technology, laparoscopic surgery has become safer and better over the years, 25 and has become one of the most common surgical options in gynaecological surgery. 26,27 Aside from technological improvements, physicians' abilities to perform minimally invasive procedures have improved over time in Canada, 8,28,29 As for regional differences in perioperative complication rates, we found that the provinces with the highest proportion of rural populations experienced the highest complications rates as compared to the province with the lowest proportion of rural populations. However, the underlying reasons for these disparities are not entirely obvious, and there is a paucity of literature on this issue.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…[22][23][24] With advances in technology, laparoscopic surgery has become safer and better over the years, 25 and has become one of the most common surgical options in gynaecological surgery. 26,27 Aside from technological improvements, physicians' abilities to perform minimally invasive procedures have improved over time in Canada, 8,28,29 As for regional differences in perioperative complication rates, we found that the provinces with the highest proportion of rural populations experienced the highest complications rates as compared to the province with the lowest proportion of rural populations. However, the underlying reasons for these disparities are not entirely obvious, and there is a paucity of literature on this issue.…”
Section: Discussionmentioning
confidence: 82%
“…An explanation for the increase in laparoscopic hysterectomy may be related to an increase of the technicity index, an indicator of the proportion of hysterectomies that are done through minimally invasive surgery, over these years in Canada. 8 In addition, the observed decline in the rate of minor conservative surgeries during the study period might be due to a change toward non-invasive methods of diagnosing endometriosis in Canada in recent years. 4 The regional variation of day surgeries might relate to differences in population characteristics as well as regional variations in healthcare access, environmental exposures, practice variations and preferences of populations.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…1 Minimal access approaches are favoured by both clinicians and patients, 2 and the proportion of hysterectomies being undertaken by a laparoscopic approach has increased substantially in many countries over the last 10 years. [3][4][5][6][7] The evidence-based medicine paradigm for surgical approaches to hysterectomy for benign disease advocates that the chosen surgical approach should be discussed with the patient by their surgeon and decided in light of the relative benefits and risks. 2 This advice is echoed by national guidelines.…”
mentioning
confidence: 99%